Síndrome de cauda eqüina produzida por melanoma - J. Lamartine de Assis; Carlos De Luccia (Arquivos de Neuro-Psiquiatria)
The authors present a case of melanoma of the cauda equina which evolved during two years, starting with pain in the lower extremities and becoming at length a cauda equina syndrome, with bilateral sciatic pain, motor and sensorial signs and bladder and rectal disturbances. The tumor was only partially removed, on account of its infiltrating character. The patient died eleven months later. He had X-ray therapy soon after the operation. Autopsy was not performed but considering the clinical data, the localization and the type of the tumor, authors believe it connected by a primary melanoma of the lombar leptomeninges. A brief review of the literature is made.